Job stress, sense of coherence and work wellness in an electricity supply organisation - S. Rothmann (South African Journal of Business Management, 2005)
The objective of this study was to test a causal model of work wellness for engineers, technicians and electricians in an electricity supply organisation. An ex post facto correlational design was used. The participants included 38 engineers, 86 technicians and 91 electricians in an electricity supply organisation. The Maslach Burnout Inventory – General Survey, the Utrecht Work Engagement Scale, the Job Stress Inventory and the Orientation to Life Questionnaire were administered. The results showed that job stress, because of job demands and a lack of support, leads to burnout. A strong sense of coherence mediated the relationship between job stress and work wellness (consisting of low burnout and high work engagement). The material described in this article is based upon work supported by the National Research Foundation under Grant number 2053344.